Risk factors and countermeasures for abnormal uterine bleeding during dienogest therapy for adenomyosis: a review - Zhang, Shiyu; Duan, Hua (Frontiers in Reproductive Health, 2025)
Adenomyosis, an estrogen-dependent disorder, requires long-term therapy as current treatments (GnRH agonists, danazol, etc.) show symptom recurrence post-discontinuation. Dienogest (DNG), a selective progesterone receptor agonist, effectively reduces adenomyosis-related pain but causes abnormal uterine bleeding (AUB) in some patients, likely due to pseudodecidual breakthrough bleeding, significantly impacting treatment compliance. This review examines risk factors for DNG-associated AUB and advances in management strategies to improve patient adherence during prolonged therapy